Surgical management of facial nerve palsy: our experience - Gupta, Devang P.; Rai, Shreya; Dinesh, K. S. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Facial nerve palsy is a challenging task to deal with in patients as it has medical as well as social implications. The aim of this study was to examine the efficacy of different surgeries for facial palsy according to pathology and the ideal time for surgery. Methods: This prospective study was conducted with the help of a structured proforma for history and examination. Defined diagnostic tests were performed and depending on complexities of cases, different surgical approaches were done. Results: A total of 50 patients with secondary facial nerve palsies were included in our study and after thorough evaluation surgical management was planned. Ninety two percent were treated with facial nerve decompression, 4% with neurorrhaphy of the nerve and another 4% with cable graft. Conclusions: High prevalence of facial nerve palsy in today’s era necessitates early diagnosis and management in order to prevent complications and thereby reducing the risk of permanent disfigurement.